Screening of hypertension among rural community of Nepal - Agrawal, Kapil H. (International Journal Of Community Medicine And Public Health, 2017)
Background: Hypertension is the commonest cardiovascular disorder, posing a major public health challenge to population in socioeconomic and epidemiological transition. The objective of the study was to determine the prevalence of hypertension in the rural community. Methods: Community-based cross sectional study was conducted in Chotkiram nagar village of Rupandehi district of Western Nepal. Door to door screening for hypertension was done using mercury sphygmomanometer. Other study variables included demographic factors only such as age and sex. The data was collected from 7th June 2016 to 20th June 2016. All the households in the village were screened and all the persons over 18 years of age in the households were subjected to blood pressure measurement. Thus the sample size comprised of all persons above 18 years of age. Total subjects enrolled were 3158. All persons above (and completed) 18 years of age and holding permanent resident status in the study area at the time of study were included in the study. Pregnant women and persons not willing to give consent were the exclusion criteria set. Though, all the participants gave their consent. Results: The prevalence of hypertension in the study is 16.2%. Conclusions: Though the hypertension is significant in the current study, the prevalence is much lower than the studies done in other parts of Nepal. More prevalence studies are required in the rural areas of Terai region.